Case report: Interleukin-17 targeted biological therapy in netherton syndrome - Mahajan, Rahul; Bakshi, Shirin; Kumar, Anoop; De, Dipankar; Handa, Sanjeev (Frontiers in Pediatrics, 2023)
Netherton syndrome (NS) is rare and multisystemic congenital skin disorder classically distinguied as a triad of congenital ichthyosiform erythroderma, trichorrhexis invaginata (TI), and an atopic diathesis. Recent advances in pathogenesis have explored the role of IL-23/Th17 pathway in NS. Herein, we present a 17 years old girl harbouring homozygous four base pair deletion in exon 26 of the SPINK5 gene, presented with pruritus, scaling, dry skin and generalized eczematous lesions. She was administered anti IL17A (subcutaneous secukinumab) therapy. The treatment was well tolerated and resulted in a favourable clinical response, reduction of the IL17A gene expression and CD4+Th17 cell population after 6 months which revealed an abrogation of Th17‐skewing during therapy.